Optimization of Carbon and Nitrogen Sources in Growth Medium and Variation in Agitation Speed in β-glucan Production of Sclerotium rolfsii - Nur Fitriyani - Nim: 10414009, Azizah
Β-glucan is a constituent compounds of fungal cell walls that act as immunomodulators. Beta-glucan is found in almost all types of fungi, including Sclerotium rolfsii. Basidiomycota mushroom which has the potential as a source of beta glucan. Utilization of Sclerotium rolfsii, supports efforts to explore the potential of local fungi as nutripharmaceutical. This study was conducted to see the effect of variations in sources and complex carbon concentrations and nitrogen sources on the growth of Sclerotium rolfsii fungi and optimization of β-glucan production with variations in agitation velocity. The research stages included (1) molecular identification of fungal isolates; (2) screening of solid medium variations in carbon sources (cornstarch, rice, and tapioca); source of nitrogen (fish broth, chicken broth, and eggs), sugar source and C concentration (5%, 10%, and 15%) and N (2.5%, 10%, and 15%) using radial growth measurements fungal mycelium and dry weight; (3) optimization of β-glucan levels in selected medium with variations in treatment of agitation speeds of 100, 125, and 150 rpm with dry weight method; and (4) quantification of water-soluble β-glucan compounds by dry weight method. From the screening results, obtained a medium that produces faster growth of fungal mycelium is a variation of the medium of maizena, fish broth, and sucrose with a ratio of the source concentration of C and N which is 15%: 10%. From the results of optimization of agitation speed, the highest levels of water-soluble β-glucan were obtained at 150 rpm agitation treatment with measured dry weight was 76.9 mg which was achieved at 168 hours incubation time, followed by dry weight of β-glucan at agitation treatment 125 rpm (61.6 grams, 192 hours) and 100 rpm agitation treatment (56.7 grams, 192 hours). From the results of this study, it is known that the medium with a carbon maize source, a source of nitrogen fish stock and a source of sucrose sugar with a 15%: 10% C: N source concentration ratio optimized at 150 rpm agitation can produce mycelium growth and β-glucan production reaching 76 , 9 mg.